Antagonistic Activity of Lactic Acid Bacteria - Tsugkiev, Boris G. (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: Studying the antagonistic activity of cultures of lactic acid bacteria strains bred at the Research Institute of Biotechnology of the Gorsky State Agrarian University compared to some representatives of pathogenic and conditionally pathogenic microflora: Staphylococcus aureus, Escherichia coli, and Proteus vulgaris. Materials and Methods: In studying the antagonistic activity of lactic acid bacteria, studies were performed with the use of the following methods of analysis generally accepted in microbiology: The method of serial dilutions in liquid nutrient medium and the method of diffusion in agar with the use of agar nutrient medium (1, 5). The material for the study was pure cultures of microorganisms’ breeding strains bred at the Research Institute of Biotechnology of the Gorsky State Agricultural University: Streptococcus salivarius RNCIM V-11174, Lactobacillus helveticus RNCIM V-11175, L. helveticus RNCIM V-11176, and S. salivarius RNCIM V-11177. Results: The article shows the data obtained in the study of antagonistic properties of lactic acid bacteria strains bred by the Research Institute of Biotechnology of the Gorsky State Agricultural University: S. salivarius RNCIM V-11174, L. helveticus RNCIM V-11175, L. helveticus RNCIM V-11176, and S. salivarius RNCIM V-11177 deposited in the All-Russian collection of industrial microorganisms of the FSUE GosNIIGenetika for S. aureus, E. coli, and P. vulgaris. It has been determined that the studied strains of lactic acid bacteria included into the starter cultures for obtaining probiotic food products contain high number of living cells of lactic acid bacteria - up to 1010 CFU/cm3 and are antagonistically active to pathogenic and conditionally pathogenic microflora. The results of the research confirm the feasibility of using pure cultures of lactic acid microorganisms bred at the Research Institute of Biotechnology of the Gorsky State Agricultural University for the preparation of bacterial starter cultures of lactic acid microorganisms due to their physiological, biochemical, and antagonistic activity. Conclusion: The results prove the feasibility of using the studied strains of lactic acid bacteria in preparing starter cultures for the production of functional probiotic products based on their high physiological, biochemical, and antagonistic activity to pathogenic and conditionally pathogenic bacteria. The studied cultures of lactic acid bacteria strains have various abilities to suppress the growth of pathogenic and conditionally pathogenic microorganisms, which should be considered in choosing lactic bacteria for preparing starter cultures and producing probiotic dairy products and functional food products.